(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article analyzes the world trends of technological transformation of machine-building companies. Innovative processes, such as related production, forecasting services and innovative service models, which are increasingly used in mechanical engineering, have been studied. The use of modern digital technologies in mechanical engineering for preventing the risks of losing relevance in the market of modern industry has been studied. The impact of the Covid-19 pandemic on the introduction of new technologies by major players in the global mechanical engineering market has been analyzed. Technological innovations have created new business models and opportunities for mechanical engineering companies. Communication and analytics allow you to create a wide range of applications for industrial technology. Although the basic principles of mechanical engineering, such as thermodynamics, fluid mechanics and machine design, still remain in force, the latest technologies are contributing to the rapid development of composites, mechatronics and nanotechnology. These new subject areas, which are the result of modern achievements, have become a prerequisite for the development of new and promising industries, including artificial intelligence and biomechatronics. The growing demand for increased production efficiency while minimizing operating costs has led to demand for new and innovative technologies. The author analyzed the pace of introduction of new technologies in the production of mechanical engineering in the world based on the number of patents filed in the field of mechanical engineering in accordance with current patent classifications. The analysis allows to clearly understand which technological trends are most common in the world market of mechanical engineering. Based on the study of the introduction of new technologies in mechanical engineering and global trends in the industry, the author substantiates the feasibility of accepting the need for deglobalization in mechanical engineering as a new norm; optimization of existing production facilities, automation and attraction of advanced digital technologies for the establishment of work processes; implementation of advanced technologies in mechanical engineering, such as artificial intelligence, Internet of Things, nanoengineering, advanced data analytics, automation of robotic processes, blockchain, robotics, cloud computing, virtual and augmented reality, 3D printing, drones, 5G, etc .; raising the qualification level of mechanical engineering workers.